Organizational Resilience of Family Business: Case Study - Tomasz Ingram; Grzegorz Glod (Institute of Economic Research (IER), 2017)
Organizational resilience, understood as an ability to survive in harsh market conditions, captures increased research consideration in recent years. The same applies to family businesses that attracted significant attention lately. Although the interest in the topic grows, there are still remaining questions to be answered. In the paper we focus on identifying factors affecting organizational abilities to adapt to dynamic, hostile and complex environment especially when disruptive events occur in the environment. Literature studies in the topic allowed development of research proposition - organizational resilience should help to survive negative occurrences in the environment and family business should focus their attention on building resilience capacity while it may allow and facilitate longevity and well-being of an organization. We illustrate this proposition with the use of two family company cases from the Silesian Voivodeship. The first is a case of a large production company that existed between 2010 and 2013, and after receiving increased growth in 2005-2012 period it went bankrupt in 2014 after two large contracts. The second is a case of a developer company from the same region that started its operation in the same period and managed to develop both its market and products in years. We compare the data flowing from interviews with the owners (that are also managers of these companies) using Eisenhardt (1989) methodology and that leads to creation of propositions for future research. Research results indicate there are several factors influencing ability to cope with critical situations. Firstly, we identified that professionalization of management of family business leads to better chances to survive in the environment. Secondly, we conclude that awareness to weak signals diminishes the probability of risky behaviors and helps to survive in dynamic, hostile environment.
Keywords: M20; H12; 330; organizational resilience; family business; case study